Representaciones, hábitos y dificultades de composición del texto escrito en estudiantes universitarios: un estudio exploratorio - Yolanda Álvarez-Sánchez; Santiago Fabregat-Barrios (Investigaciones Sobre Lectura)
This article presents an exploratory study into the assumptions, habits of composition and principal difficulties that university students in the study declare to have in regard to the composition of written texts. It is a qualitative study elaborated from a series of semi-structured interviews used as a method of data collection. Once the analysis and categorisation of the data is complete, we present the system of beliefs of the participants regarding professional and academic writing. We identified their most relevant difficulties and make clear what must be taken into consideration when proposing actions which objective is to improve writing competencies in the area of Tertiary Education.